THE SPREAD OF TOXOCARIASIS IN DOGS AND CATS IN TYUMEN AND THE EFFICIENCY OF THERAPEUTIC PRODUCTS - Domatsky1, Vladimir; Sivkova, Elena; Siben, Anna (Revista Inclusiones, 2019)
The article presents the results of studying the spread, the seasonal dynamics of toxocariasis in dogs and cats in Tyumen, and the degree of animals’ infestation depending on the age, gender, feeding type, and living conditions. The degree of soil and vegetable samples contamination with the eggs of Toxocara has been shown. The results of testing the efficiency of anthelmintic drugs for the treatment of toxocariasis is dogs and cats are provided.